Stress-strain relationship for very-high strength concrete (>100 MPa) confined by lateral reinforcement. (15th December 2018) - Kristombu Baduge, Shanaka; Mendis, Priyan; Ngo, Tuan
Highlights: Failure mechanisms and parameters for stress-strain behaviour of VHSC are identified. A theoretical stress-strain model was developed for VHSC confined by lateral steel. The new model can predict the stress-strain behaviour more accurately. Abstract: Stress–strain models of confined and unconfined VHSC considered as key inputs for analytical programs that predict the full-range moment–curvature behaviour of VHSC columns, which can subsequently evaluate the ductility of columns. Only very few theoretical models are available in the literature to predict stress-strain behaviour of confined VHSC, and those theoretical models are not valid up to a compressive strength of 150 MPa or higher. In this paper, experimental stress-strain behaviour of twenty-two very-high strength concrete samples with compressive strengths in a range of 120–160 MPa confined by lateral reinforcement is presented and they are used to develop a novel stress-strain model for confined VHSC. Furthermore, the study proposed a novel theoretical approach to predict stress-strain behaviour of concrete considering shear decay at the failure plane, passive confinement of transverse reinforcement, and dowel action of reinforcement. Using the above phenomenon, an analytical model to predict the stress-strain behaviour for VHSC is developed. From a comparison between the experimental results and existing stress-strain models, it was concluded that the new theoretical approach can predict stress-strain behaviour up to 160 MPa satisfactorily and perform better than other models.